“Fatigue Analysis Of Epoxy Composite Material Reinforcement On Propeller Shaft” - Kashinath H. Munde, et al. (Mathematical Statistician and Engineering Applications, 2022)
Propeller shaft, also known as propeller shaft is the most important component to any power transmission application; automotive propeller Shaft is one of this. A propeller shaft is a mechanical part that transmits the generated torque by a vehicle’s engine into motive force which is usable to propel the vehicle. Substituting composite structures for metallic which is structures has many advantages because of higher specific stiffness and strength of composite materials. This work deals with the conventional replacement of steel propeller shafts with fiberglass epoxy composite propeller shaft for an automotive application. The parameters of design were optimized with the objective of minimizing the weight of a propeller shaft. The design optimization also improves the performance of propeller shaft. Present work deals with FEA analysis of composite shaft with different degree of orientation of glass fibers. It includes the modeling of shaft in CATIA. The meshing and boundary condition application will be carried using Hypermesh, Fatigue analysis of composite shaft will be carried out using ANSYS.